Modulation of ventilatory reflex control by cardiac resynchronization therapy - Cundrle, Ivan; Johnson, Bruce D; Rea, Robert F; Scott, Christopher G; Somers, Virend K; Olson, Lyle J (Journal of cardiac failure, 2015)
BACKGROUND: Heart failure (HF) is characterized by heightened sensitivities of the CO2 chemoreflex and the ergoreflex which promote increased ventilatory drive manifested as increased minute ventilation per volume of expired CO2 (VE/VCO2). The aims of this study were to evaluate the effects of cardiac resynchronization therapy (CRT) on carbon dioxide (CO2) chemosensitivity and the arterial CO2 setpoint. METHODS AND RESULTS: Consecutive HF patients (n = 35) who underwent clinically indicated CRT were investigated by means of cardiopulmonary exercise testing and CO2 chemosensitivity evaluation with the use of a rebreathe method before and 4-6 months after CRT. Pre- and post-CRT measures were compared with the use of either paired t test or Wilcoxon test. Decreased peak VE/VCO2 (44 ± 10 vs 40 ± 8; P < .01), CO2 chemosensitivity (2.2 ± 1.1 vs 1.7 ± 0.8 L min(-1) mm Hg(-1); P = .04), and increased peak end-tidal CO2 (29 ± 5 vs 31 ± 5 mm Hg; P < .01) were also observed after CRT. Multivariate analysis adjusted for age and sex showed the decrease of peak VE/VCO2 from before to after CRT to be most strongly associated with the increase of peak end-tidal CO2 (β = -0.84; F = 21.5; P < .0001). CONCLUSIONS: Decrease of VE/VCO2 after CRT is associated with decreased CO2 chemosensitivity and increase of the arterial CO2 setpoint, which is consistent with decreased activation of both the CO2 chemoreflex and the ergoreflex.
Keywords: senioři; plicní ventilace; Exercise Test; spotřeba kyslíku; Oxygen Consumption; Carbon Dioxide; Middle Aged; mužské pohlaví; Blood Gas Analysis; Heart failure; Follow-Up Studies; oxid uhličitý; následné studie; ženské pohlaví; cardiopulmonary exercise testing; Humans; analýza krevních plynů; chemosensitivity; lidé středního věku; srdeční selhání; zátěžový test; Cardiac Resynchronization Therapy; srdeční resynchronizační terapie; Pulmonary Ventilation; Female; Aged; Heart Failure; lidé; Male; pacing